LPS Remodeling Triggers Formation of Outer Membrane Vesicles in Salmonella - Wael Elhenawy (American Society for Microbiology, 2016)
ABSTRACT Outer membrane vesicles (OMV) are proposed to mediate multiple functions during pathogenesis and symbiosis. However, the mechanisms responsible for OMV formation remain poorly understood. It has been shown in eukaryotic membranes that lipids with an inverted-cone shape favor the formation of positive membrane curvatures. Based on these studies, we formulated the hypothesis that lipid A deacylation might impose shape modifications that result in the curvature of the outer membrane (OM) and subsequent OMV formation. We tested the effect of lipid A remodeling on OMV biogenesis employing Salmonella enterica serovar Typhimurium as a model organism. Expression of the lipid A deacylase PagL resulted in increased vesiculation, without inducing an envelope stress response. Mass spectrometry analysis revealed profound differences in the patterns of lipid A in OM and OMV, with accumulation of deacylated lipid A forms exclusively in OMV. OMV biogenesis by intracellular bacteria upon macrophage infection was drastically reduced in a pagL mutant strain. We propose a novel mechanism for OMV biogenesis requiring lipid A deacylation in the context of a multifactorial process that involves the orchestrated remodeling of the outer membrane. IMPORTANCE The role of lipid remodeling in vesiculation is well documented in eukaryotes. Similarly, bacteria produce membrane-derived vesicles; however, the molecular mechanisms underlying their production are yet to be determined. In this work, we investigated the role of outer membrane remodeling in OMV biogenesis in S. Typhimurium. We showed that the expression of the lipid A deacylase PagL results in overvesiculation with deacylated lipid A accumulation exclusively in OMV. An S. Typhimurium ΔpagL strain showed a significant reduction in intracellular OMV secretion relative to the wild-type strain. Our results suggest a novel mechanism for OMV biogenesis that involves outer membrane remodeling through lipid A modification. Understanding how OMV are produced by bacteria is important to advance our understanding of the host-pathogen interactions.